1995
DOI: 10.1161/01.res.77.6.1143
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Transmural Heparin Transport in the Rat Abdominal Aorta After Local Vascular Delivery

Abstract: Local vascular drug delivery systems provide elevated concentrations in target arterial tissues, while minimizing systemic side effects. Drug can now be released to isolated arterial segments from the endovascular or perivascular aspects of the blood vessel, yet the forces that determine drug distribution and deposition for these different modes of delivery have not been rigorously investigated. This study examines mechanisms of transmural transport of a model vasoactive drug, heparin, and compares estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 27 publications
4
88
0
Order By: Relevance
“…I t now appears that the success of drug-eluting stents is predicated to as great a degree upon the extent of drug deposition and distribution through the arterial wall as virtually any other factor (1)(2)(3)(4)(5). The biological effects of a candidate drug are essential, but, ultimately, tissue residence time will determine effect and toxicity (6,7).…”
mentioning
confidence: 99%
“…I t now appears that the success of drug-eluting stents is predicated to as great a degree upon the extent of drug deposition and distribution through the arterial wall as virtually any other factor (1)(2)(3)(4)(5). The biological effects of a candidate drug are essential, but, ultimately, tissue residence time will determine effect and toxicity (6,7).…”
mentioning
confidence: 99%
“…13 The fast phase is considered to represent extracellularly bound LPL, whereas the delayed phase may originate from a separate compartment. Because heparin has been demonstrated to traverse the endothelial barrier, 14 we suggested that conventional Langendorff retrograde perfusion of the heart with heparin can release not only LPL bound to the luminal side of the capillary endothelium but also that present at the abluminal surface, the interstitial space, and the myocyte surface. Interestingly, in streptozotocin (STZ)-diabetic rats, the initial fast phase of heparin-releasable LPL activity was significantly elevated after 2 or 12 weeks of hypoinsulinemia, whereas the second, or delayed, phase of LPL release was absent.…”
mentioning
confidence: 99%
“…A number of models have appeared in the literature [9][10][11][12][13][14][15][16]. The individual models take account of different physical processes.…”
Section: Impact Of Balloon Permeability On Drug Deliverymentioning
confidence: 99%